IMAGENS DA INFÂNCIA NA ESCOLA PÚBLICA DE SÃO LUÍS/MA: o lugar da criança no imaginário de professores - Fonteles, Lia Silva (2013)
This research develops a comprehensive study about teachers imaginary of children in a public kindergarten school in São Luís / MA. For this, seeks to check the images present in the narratives, drawings, reports of childhood, and other manifestations of the teachers; understand childhood revealed by these images and to analyze what they suggest about the place reserved for this phase of life for researched group. The path taken to that weaving is given by comprehensive phenomenology, based on hermeneutics, the main theoretical is Gilbert Durand´s (1993, 2002, 2010) anthropology of the imaginary and support discussions on specific areas of the human sciences: Childhood Sociology, Anthropology of Children, Developmental Psychology and Pedagogy, performing a convergence of these theories to the understanding of the researched object. Images were collected from the questionnaires, conducting an interview, the representation of childhood through plastic images and narrative on such images. The subjects of this research were six (6) teachers at a public school of that city. We found that in the group studied appear imaginary elements that reveal a balance with regard to the symbolic representation of childhood, but in general, we find that there is a greater tendency to a daytime representation, with an antagonistic appreciation of child. The understanding of the images revealed attitudes of teachers towards the child in the social context, pointing a symbolic place for childhood in the imaginary of the group.